Heterogeneous mechanisms of pulmonary congestion in hypertrophic cardiomyopathy unmasked by comprehensive exercise stress echocardiography. (3rd October 2022) - Palinkas, E D; Re, F; Peteiro, J; Tesic, M; Palinkas, A; Torres, M A R; Djordjevic Dikic, A; Beleslin, B; Van De Heyning, C M; D'Alfonso, M G; Mori, F; Ciampi, Q; et al.
Abstract: Background: B-lines detected by lung ultrasound (LUS) during exercise stress echocardiography (ESE), indicating pulmonary congestion, are present in 1 out of 3 patients with hypertrophic cardiomyopathy (HCM). Aim: To assess the functional and anatomical correlates of exercise B-lines in HCM. Methods: We enrolled 191 HCM patients (age 53±15 years, 123 males) consecutively referred for ESE (treadmill in 74, bicycle in 117 patients) in 11 quality-controlled centers from 8 countries. ESE assessment at rest and peak stress included: left ventricular (LV) outflow tract gradient, left atrial (LAVi) and LV end-diastolic volume index (EDVi), mitral regurgitation (MR, score from 0 to 3); E/e'; systolic pulmonary arterial pressure (SPAP) and LV force (LV outflow tract gradient+systolic blood pressure/LV end-systolic volume). B-lines at rest and at peak exercise were assessed by LUS with the 4-site simplified scan. B-lines positivity was considered if the sum of detected B-lines was ≥2. Results: LUS was feasible in all subjects. B-lines were present in 55 (29%) patients during stress. When compared to patients without stress B-lines (n=136), patients with B-lines (n=55) at peak exercise had lower peak EDVi (43±17 vs 52±18 ml/m 2, p=0.003) higher peak E/e' (16±6 vs 12±5, p<0.001), increase in MR (34 vs 12%, p=0.001), greater stress LAVi (43±14 vs 37±14 ml/m 2, p=0.003) and stress SPAP (56±18 vs 40±12 mm Hg p<0.0001): see Figure. Among baseline parameters, the number of B-lines (OR: 7.53, 95% CI 1.21–46.72 p=0.03), LAVi (OR: 1.05, 95% CI 1.00–1.09 p=0.04), and LV force (OR: 1.36, 95% CI 1.04–1.79 p=0.03) were the independent predictors of exercise pulmonary congestion. Conclusion: HCM patients with pulmonary congestion on exercise show different, and not mutually exclusive mechanisms of diastolic dysfunction and worsening mitral regurgitation. These different hemodynamic mechanisms may require personalized therapeutic actions beyond a pulmonary decongestion therapy with diuretics. Funding Acknowledgement: Type of funding sources: None.